Limitation of Water-Soluble Tetrazolium Salt for the Cytocompatibility Evaluation of Zinc-Based Metals - Peijun Zhu (MDPI AG, 2021)
Zinc (Zn) and its alloys have been regarded as promising biodegradable metals. The standardized cytotoxicity evaluation is a mandatory step to screen the biocompatibility of novel Zn and its alloys. Nevertheless, the suitability of the tetrazolium-based assay in the direct contact test for some metallic biomaterials (i.e., magnesium and manganese) is questionable. In this study, our results demonstrate an obvious inconsistency between qualitative observation via fluorescence staining and quantitative assessment using water-soluble tetrazolium salt (CCK-8). Subsequent experiments revealed that Zn and pre-treated Zn can directly convert tetrazolium salts to formazan, falsifying the cytotoxicity results. Therefore, we conclude that the CCK-8 assay is not suitable for evaluating the cytotoxicity of biodegradable Zn-based metals in the direct contact test.